Clean energy generator : redesign - Chan, KaChun. (2013)
Fossil fuel are still mainly used to generate electricity which is not good for the environment as it increases pollution and the fuel sources is depleting, hence it is essential to find viable alternative to replace fossil fuelled power plants.